Pengaruh Perilaku dan Status Gizi terhadap Kejadian TB Paru Di Kota Pekalongan - ,, Supriyo; Baequny, Ahmad; Hidayati, Sri; Harnany, Afiyah Sri (Universitas Pekalongan, 2013)
Background : Burden countries toward Pulmonary TBC, one of them is Indonesia. Data of WHO shows that Indonesia, every years is found 580.000 the new sufferers of Pulmonary TBC and the number of death because of Pulmonary TBC reaches 140.000 per year. The large number of sickness placed Indonesia as a country that has the most Third Pulmonary TBC sufferers in the world, after China and India, the prevalence reaches up to 225/100.000 inhabitant. In Pekalongan, according to the Puskesmas report shows there is an increase Pulmonary TBC case year by year, we can find it in a range of sufferers BTA tuberculosis positive findings or Case Detection Rate (CDR) in 2009 registered 88,7% in prevalence is 81,43%, in 2010 is 97,81% in prevalence is 78,73%, in 2011 there is 132, 78% in prevalence 92,79%. This case shows that in Pekalongan, the Pulmonary TBC disease case is still high. Some BTA pulmonary tuberculosis positive cases that be found and cured in Pekalongan in 2011 is 229 sufferers. This number is categorized as high, and the majority sufferers are from the incapable socioeconomic family, so that they have malnutrition tendency. The aim of this research is to know the influence of behavior and nutrient status toward the case of Pulmonary TBC in Pekalongan. This research is a kind of case control research. The independent variable that being researched are behavior and nutrient status, and the sufferers’ contact are as confounding variable.Methods : This research wad done to 70 respondents’ sufferers of TBC with BTA (+) as case and 70 respondents not sufferers as a control to the same characteristics. Results : The result of the finding is that there is no influence between behavior influence toward Pulmonary TBC and the percentage is p= 0,285. Then, there is an influence of nutrient status toward case of Pulmonary TBC and the percentage is p= 0,000 and OR= 7.583 and also there is an influence of sufferers’ contact toward the case of Pulmonary TBC and the percentage is p= 0,049 and OR= 4,387. The researcher suggests doing the effort to increase the crawl of sufferers Pulmonary TBC to increase the new case of finding, increase the hygienic and healthy behavior and increase the citizens’ nutrient status. Key words: behavior, nutrient status, Pulmonary TBC.